2017
DOI: 10.1038/s41467-017-02256-y
|View full text |Cite
|
Sign up to set email alerts
|

Redox-switchable breathing behavior in tetrathiafulvalene-based metal–organic frameworks

Abstract: Metal–organic frameworks (MOFs) that respond to external stimuli such as guest molecules, temperature, or redox conditions are highly desirable. Herein, we coupled redox-switchable properties with breathing behavior induced by guest molecules in a single framework. Guided by topology, two flexible isomeric MOFs, compounds 1 and 2, with a formula of In(Me2NH2)(TTFTB), were constructed via a combination of [In(COO)4]− metal nodes and tetratopic tetrathiafulvalene-based linkers (TTFTB). The two compounds show dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
123
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(137 citation statements)
references
References 37 publications
6
123
0
Order By: Relevance
“…Each group of five TTFs consists of two sets of dimers (TTF1 and TTF2) and an orthogonal TTF (TTF3). Though this arrangement contrasts with the parallel π‐stacking modes of other TTFTB MOFs, it is somewhat reminiscent of the κ packing arrangement, consisting of orthogonal TTF dimers, found in many organic metals and superconductors ,. Close S⋅⋅⋅S contacts as short as 3.72 Å are present between all S atoms within the dimers in Tm 6 (TTFTB) 5 .…”
Section: Figurementioning
confidence: 79%
See 2 more Smart Citations
“…Each group of five TTFs consists of two sets of dimers (TTF1 and TTF2) and an orthogonal TTF (TTF3). Though this arrangement contrasts with the parallel π‐stacking modes of other TTFTB MOFs, it is somewhat reminiscent of the κ packing arrangement, consisting of orthogonal TTF dimers, found in many organic metals and superconductors ,. Close S⋅⋅⋅S contacts as short as 3.72 Å are present between all S atoms within the dimers in Tm 6 (TTFTB) 5 .…”
Section: Figurementioning
confidence: 79%
“…Whereas the assembly of most MOFs is driven by the formation of inorganic secondary building units (SBUs), our group has recently shown that the organic ligands can also direct structure through the formation of supramolecular π interactions that define an organic SBU, as demonstrated with the isolation of an unprecedented topology in MIT‐25 . The latter is based on the tetrathiafulvalene tetrabenzoate (TTFTB) linker, which forms MOFs with diverse topologies, all of which exhibit strong π interactions . In addition to their structure‐defining roles, these interactions lead to several desirable physical properties, including electrical and proton conductivity, and redox‐switchable breathing behavior .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…To improve the conductivity of MOFs, several strategies have been developed; the most successful installs charge carriers through chemical redox of either the metal/node or ligand. [16][17][18][19][20] However, chemical stability of the framework is another critical property required for electrically conductive MOF applications. Examination of the literature reveals that frameworks featuring confined ceramic nodes (e.g.…”
mentioning
confidence: 99%
“…With this in mind, TTF-containing ligands (e.g., tetrathiafulvalene tetrabenzoic acid, TTFTB) have been incorporated into MOFs. 17,[30][31][32][33][34][35] The resultant materials were shown to be modest electrical conductors, [36][37][38][39][40] with the highest performing materials featuring closely packed TTF subunits repeating throughout the crystal.…”
mentioning
confidence: 99%